1982
DOI: 10.1038/299161a0
|View full text |Cite
|
Sign up to set email alerts
|

Modifier role of internal H+ in activating the Na+–H+ exchanger in renal microvillus membrane vesicles

Abstract: The intracellular pH in animal cells in generally maintained at a higher level than would be expected if H+ were passively distributed across the plasma membrane. In a wide variety of cells including sea urchin eggs, skeletal muscle, renal and intestinal epithelial cells, and neuroblastoma cells, plasma membrane Na+-H+ exchangers mediate the uphill extrusion of H+ coupled to, and thus energized by, the downhill entry of Na+. Plasma membrane vesicles isolated from the luminal (microvillus, brush border) surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
393
6
4

Year Published

1986
1986
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 681 publications
(434 citation statements)
references
References 14 publications
31
393
6
4
Order By: Relevance
“…Aronson and coworkers proposed that cytoplasmic H+ acts as an allosteric activator of the Na+/H+ exchanger (Aronson et al, 1982). It has been suggested that the antiport molecule has on its cytoplasmic face two proton-binding sites that are separate and functionally independent.…”
Section: Mechanisms Involved In the Regulation Of Intracellular Ph Namentioning
confidence: 99%
See 1 more Smart Citation
“…Aronson and coworkers proposed that cytoplasmic H+ acts as an allosteric activator of the Na+/H+ exchanger (Aronson et al, 1982). It has been suggested that the antiport molecule has on its cytoplasmic face two proton-binding sites that are separate and functionally independent.…”
Section: Mechanisms Involved In the Regulation Of Intracellular Ph Namentioning
confidence: 99%
“…When this site is occupied, a conformational change is triggered, activating the exchanger. A distinct H+-transport site mediates the net extrusion of H+ once the exchanger is activated (Aronson et al, 1982;Aronson, 1985).…”
Section: Mechanisms Involved In the Regulation Of Intracellular Ph Namentioning
confidence: 99%
“…The exchangers are allosterically activated by cytosolic H ϩ , promoting the rapid extrusion of acid once intracellular pH drops below a threshold level (33). This feature is conserved in the NHE isoforms examined to date (NHE1-NHE3), although the apparent H ϩ sensitivity, which determines the "set point" for activation, varies between isoforms (30, 31).…”
Section: Basic Functional Propertiesmentioning
confidence: 99%
“…The viability of cells in an acidic microenvironment also depends on the activity of membrane-based exchangers that regulate pHi . Two major exchangers known to be involved in the regulation of pH, under acidic conditions are the Na+/H+ antiport (Johnson and Epel, 1976;Aronson et al, 1982;Moolenaar et al, 1984) and the Na+-dependent HCO3 /Cl1 exchanger (Thomas, 1977;L'Allemain et al, 1985;Cassel et al, 1988). The former is inhibited by amiloride and its substituted analogues, and the latter is inhibited by stilbene derivatives such as DIDS (4,4-diisothiocyanstilbene 2,2-disulphonic acid).…”
mentioning
confidence: 99%